Integrating Case-Based Reasoning in Job Matching System for Pre-selection Process of Recruitment - Norhasimah, Mustafa (2009)
The progress of Internet and World Wide Web technology brings the movement of traditional recruitment process to web based recruitment. Applying job matching approach automatically will bring benefit to both job seekers and employers. For the employer, the costs of manually preselecting potential candidates have risen and employers are searching for means to automate the preselecting of candidates. A few techniques could be applied in order to implement job matching process such as using fuzzy matching, semantic, rule-base reasoning and case–based reasoning (CBR). This study aims to demonstrate that CBR could be integrated in job matching to recommend the best candidate suitable with the job requirement using similarity measurement. As a result, a prototype called Intelligent Agent Dot Com (IADC) using CBR engine for matching purposes has been developed, validated and evaluated in this study. The finding through validation and evaluation phase indicates that IADC is reliable to assist employer in the pre-selection process during recruitment. In fact, the pre-selection of candidates has become easier than the manual process.